2015
DOI: 10.5812/hepatmon.24366
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon α Therapy in Chronic Delta Hepatitis: A One-Center Experience

Abstract: Background:The only established therapy for chronic viral delta hepatitis, the most severe form of viral hepatitis is treatment with pegylated-interferon α (Peg IFN α).Objectives:In this study, we aimed to determine the efficacy of pegylated-interferon α 2a (Peg-IFN α 2a) and 2b (Peg IFN α 2b) in the treatment of patients infected with chronic delta hepatitis virus.Patients and Methods:The sample size was based on available patients potentially to be recruited. Data of 63 patients receiving either Peg IFN alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Our results moderately also agreed with the Heidrich et al results who observed that chronic HBV DNA viremia becomes undetectable in some patients after 48 weeks of treatment (Heidrich et al, 2014). A recent study also observed similar results after 52 weeks of therapy (Bahcecioglu et al, 2015). Our model predicts an overall decline of HDV viremia after 12 months comparable to that achieved by some patients in the study by Guedj et al (2014); however there are some differences in the early decline, since our model predicts a monophasic rather than a biphasic decline.…”
Section: Discussionsupporting
confidence: 95%
“…Our results moderately also agreed with the Heidrich et al results who observed that chronic HBV DNA viremia becomes undetectable in some patients after 48 weeks of treatment (Heidrich et al, 2014). A recent study also observed similar results after 52 weeks of therapy (Bahcecioglu et al, 2015). Our model predicts an overall decline of HDV viremia after 12 months comparable to that achieved by some patients in the study by Guedj et al (2014); however there are some differences in the early decline, since our model predicts a monophasic rather than a biphasic decline.…”
Section: Discussionsupporting
confidence: 95%
“…Late Virologic Response (LVR) was the absence of detection of HDV RNA in the blood 48 weeks after treatment initiation [20,21].…”
Section: Definition Of Operational Termsmentioning
confidence: 99%
“…Numerous controlled clinical trials have been conducted since the early 1990s testing various interferon-containing treatment regimens in CHD subjects [ 39 ]. Despite these efforts, disappointing response rates were generally observed (~up to 43%) after a 1 to 2 year treatment course [ 40 , 41 , 42 , 43 ]. At least one large observational retrospective study is also closely aligned with this conclusion [ 43 ].…”
Section: Hdv Biologymentioning
confidence: 99%